Employee LEAPS : leveraging engagement by applying positive strategies - Phillips, Kevin E. (Human resource management and organizational behavior collection., 2016)
A recent Gallup Study estimated that 7 in 10 American workers are "actively disengaged" or "not engaged" while at work, costing the economy between $450 and $550 billion per year. This book has been written to increase employee engagement and optimize workplace performance. By harnessing the power of engagement and nurturing people's innate desire to be captivated by the activities in which they are involved, Employee LEAPS has the potential to transform organizations and facilitate remarkable outcomes that extend far beyond what could be achieved otherwise. More specifically, Employee LEAPS presents appropriate perspective on why companies with dedicated employees are more successful, positive strategies that can be used to generate engagement, and most importantly, a step-by-step process for developing your organization's customized Engagement Plan. Additionally, the book presents 47 Positive Engagement Practices that can be used in your organization. If you are interested in increasing employee engagement and optimizing workplace performance, this is the book for you. The author provides astute direction on how to increase organizational capacity and unleash talent, enabling businesses to produce exceptional results.